Japan's Forgotten God: Jūzenji in Medieval Texts and the Visual Arts - Porath, Or (Religions, 2022)
This study examines Jūzenji 十禅師, a medieval god worshiped within the Sannō cult at Hie Shrine during the twelfth to sixteenth centuries. The article demonstrates that Tendai thinkers promoted Jūzenji to a supreme ontological status since his liminal and ambivalent character afforded him the unique role of redirecting the sinful desires of the flesh into awakening. Three different figures promoted Jūzenji. First, the Tendai abbot Jien 慈円 (1155–1255) constructed ritual programs that raised Jūzenji to the apogee of the Sannō Shintō pantheon, which combined with engi literature concerning Jien’s sexuality, permitted the re-envisioning of Jūzenji as a libidinal god. Second, the preceptors of Mt. Hiei (kaike 戒家) transformed Jūzenji into an embodiment of the precepts, which enabled Jūzenji to encapsulate morality and thereby render sexual sins null. Third, Tendai Sannō Shintō theologians (kike 記家) interweaved Jūzenji with the doctrine of the threefold truth (santai 三諦), which became the basis of the Taimitsu sexual initiation known as Chigo Kanjō 児灌頂. As such, this article offers an important case study whereby a subsidiary god outshines its own godhead for the purpose of legitimating sexuality.